KARAKTERISTIK KEMAMPUAN PEMECAHAN MASALAH SISWA KELAS VIII DI KABUPATEN BANDUNG BARAT - Pujiyanti Sahri; Jozua Sabandar; Aflich Yusnita Fitrianna (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This study aims to determine the characteristics of the problem solving abilities of class VIII students in a junior high school in West Bandung Regency. In this study using a qualitative descriptive research method. Data collection techniques in this study were in the form of problem-solving skills tests and interviews. The results of the tests and interviews were analyzed for each item based on Polya's ability to solve problems. The test instruments used were test descriptions of problem solving questions and interview guidelines. Based on data analysis that refers to indicators of problem solving ability, the research results obtained that the indicator of solving problems obtained results of 87%, and on the other 3 indicators namely understanding the problem obtained results of 55%, planning problem solving obtained results of 30% and buying back problems obtained results of 20%. Thus, there were still a number of errors found in the results of student answers in solving problem-solving solutions including: not listing what was known, asked, and not describing these elements, the process of planning problem solving was not systematic, did not understand problems, errors in calculating answers, and not writing conclusions from the results of the settlement. Students are not used to solving problems in the form of stories with complex daily life contexts, which is a factor that is often found in junior high school students.